Depressive disorders: Defi nitions, contexts, differential diagnosis, neural correlates and clinical strategies - Giulio Perrotta (Archives of Depression and Anxiety - Peertechz Publications, 2019)
Starting from the categorical defi nitions of "depressive disorders", we proceeded to list the individual forms provided by the DSM-V, with a particular focus on historical, clinical, neurobiological and therapeutic profi les, concluding the analysis of the possible strategies to be used to fi nalize the resolutions to problems arising from the disorder in question. the fi rst in 2030, resulting in a substantial loss of productivity per day of illness and increased mortality. In other words, depressed patients will have a higher work and social disability than diseases such as hypertension, diabetes, arthritis and low back pain (Murray CJL, Lopez AD, Lancet 1997; WHO, 2004) (...)>> [2].